Building the Collections of the California Digital Library - Susan S. Starr (Issues in Science and Technology Librarianship)
In October of 1997, the University of California announced the creation of the California Digital Library, an initiative that will harness the power of digital technologies to make the University's unique library and information resources more widely available to all Californians, as well as provide leadership and support to other segments in order to enhance access to digital information resources throughout the state. In addition to providing valuable new services to the people of California, the California Digital Library will enhance library service to UC faculty and students while supporting the library system during its transition to the digital future. This article will discuss the main elements of the California Digital Library initiative.